ANALYSIS OF NUTRITIONAL STATUS AND RISK FACTORS IN PEDIATRIC PATIENTS WITH INTESTINAL OSTOMY - Madariaga, Marcella Leona Pinheiro; Haack, Adriana; Beckmann, Lívia Gurgel Diniz; Horino, Aline Melo Nascimento (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To evaluate the nutritional status, food consumption and nutritional, clinical, and social risk factors of pediatric ostomy patients treated as outpatients at a public hospital in Brasília, DF, Brazil. Method: This is a cross-sectional, quantitative, and analytical study performed with ostomized children, of both sexes, under 10 years old. A diagnosis of nutritional status was performed using various nutritional assessment instruments, and food consumption was evaluated. Results: A total of 24 children was attended with a mean age of 10.29 months. The most common ostomy was colostomy (54%), and the most frequent reason for making a stoma was anorectal anomaly. High frequencies of nutritional deficits were found. The association between nutritional status and the reason for making the stoma was statistically significant (p = 0.036). Conclusion: The underlying cause for making the stoma can lead to impaired nutritional status. High frequencies of nutritional deficits were found, since part of the children were below the thinness line. Most patients use specialized infant formula. It was possible to observe a high consumption of ultra-processed foods in children who have already started eating solids.